The Outcome of Presidential Elections in Afghanistan and the Future of Political Transit - I. Safranchuk (Международная аналитика, 2015)
This article is devoted to one of the most complicated issues of the regional politics in the Central and South Asia – the presidential elections in Afghanistan in 2014. The article studies the outcome and results of the presidential elections, political and juridical dilemmas around these results, the consequences of so called «political transit» in Afghanistan.